The Interaction Between Boundary Layer and Convection Schemes in a WRF Simulation of Post Cold Frontal Clouds Over the ARM East North Atlantic Site. Issue 8 (25th April 2019) - Lamraoui, Fayçal; Booth, James F.; Naud, Catherine M.; Jensen, Michael P.; Johnson, Karen L.
Abstract: The correct representation of low‐level midlatitude clouds found in the wake of cold fronts strongly relies on the representation of planetary boundary layer (PBL) and convection processes, which are typically parameterized separately in numerical models. Using the Weather Research and Forecasting Model (WRF), this study investigates how distinct pairs of PBL and convection parameterization schemes represent cloud fraction in the post cold frontal region. The simulations focus on the region of the Department of Energy Atmospheric Radiation Measurement (ARM) Eastern North Atlantic observation site in the Azores Islands in the wake of a cold front that passed on 25 December 2015. Different PBL and convection schemes are combined to create 12 distinct configurations. The main differences between the selected physical parameterizations are the strength of vertical mixing and the entrainment. The simulations produce a wide range of cloud fractions, where some configurations significantly underestimate while others clearly overestimate satellite and surface‐based estimates of cloud fraction. A skill score is used to quantitatively assess the performance of each configuration with respect to ground‐based radar data. The key processes that are found to significantly impact the cloud fraction distribution are the strength of the PBL decoupling, the vertical wind shear, entrainment and detrainment rates in shallow convection, and the occurrence of drizzle. This indicates that to successfully simulate post cold frontal clouds, modeled physics must balance strong internal vertical mixing and weak exchange with the free troposphere. For this case study, cloud fraction was more sensitive to the choice of convection scheme than PBL scheme. Key Points: The key processes that affect modeled post cold frontal cloud fraction are the boundary layer decoupling, vertical wind shear, entrainment/detrainment, and drizzle Modeled physics must balance strong internal vertical mixing and weak exchange with the free troposphere No single mechanism can explain the differences in cloud fractions across an ensemble of different boundary layer/convection configurations